Gay male academics in UK business and management schools: Negotiating heteronormativities in everyday work life - Ozturk, Mustafa Bilgehan; Rumens, Nick (British journal of management, 2014)
This paper contributes to a neglected topic area about lesbian, gay, bisexual and trans people's employment experiences in UK business and management schools. Drawing on queer theory to problematize essentialist notions of sexuality, we explore how gay male academics negotiate and challenge discourses of heteronormativity within different work contexts. Using in‐depth interview data, the paper shows that gay male academics are continually constrained by heteronormativity in constructing viable subject positions as ‘normal’, often having to reproduce heteronormative values that squeeze opportunities for generating non‐heteronormative ‘queer’ sexualities, identities and selves. Constructing a presence as an openly gay academic can invoke another binary through which identities are (re)constructed: as either ‘gay’ (a cleaned up version of gay male sexuality that sustains a heteronormative moral order) or ‘queer’ (cast as radical, disruptive and sexually promiscuous). Data also reveal how gay men challenge organizational heteronormativities through teaching and research activities, producing reverse discourses and creating alternative knowledge/power regimes, despite institutional barriers and risks of perpetuating heteronormative binaries and constructs. Study findings call for pedagogical and research practices that ‘queer’ (rupture, destabilize, disrupt) management knowledge and the heterosexual/homosexual binary, enabling non‐heteronormative voices, perspectives, identities and ways of relating to emerge in queer(er) business and management schools.